A Global Assessment of the Economic Effects of Export Taxes. (2nd May 2013) - Laborde, David; Estrades, Carmen; Bouët, Antoine
Abstract This paper uses a new detailed global data set on export taxes at the HS6 level and the MIRAGE global Computable General Equilibrium model to assess the impact of export taxes on the world economy. We find that removing export taxes would have worldwide effects: the average export tax on global merchandise trade was 0.48 per cent in 2007, with the bulk of these taxes imposed on energy products. The removal of these taxes would increase global welfare by 0.23 per cent, a larger figure than expected gains from the Doha Round. Both developed and emerging economies, such as China and India, would gain from such policies even if they currently impose export taxes. Medium and small food‐importing countries without market power (such as the least‐developed countries) would also benefit from the elimination of export restrictions – especially during food crisis situations. Both the energy sector and the export taxes implemented by the Commonwealth of Independent States countries appear to play a critical role in the overall economic impact of such a policy change. However, the fact that some countries, such as Argentina, would experience income losses due to such a policy change is a major challenge to overall positive reform in this area.